The Birtish Colonialism and Resistance in Balochistan - Baloch, Prof.Dr.Munir Ahmed (Hanken, 2009)
Resistance has been a part and parcel of the Baloch nation against the despotic rulers throughout the history for the protection of their lives, land, honor and disgrace. The objective of this paper is to show the resistance of the Baloch nation against the British Colonial rule in different areas of Balochistan and the subjugation of Khanates of Kalat. The battle of Gokprosh, a clear chapter of resistance against the British Raj, fought between the Biritish army and Mir Baloch Khan Noshirwani, will also be focused.